An easy-to-fabricate low-temperature TiO2 electron collection layer for high efficiency planar heterojunction perovskite solar cells - Conings, B.; Baeten, L.; Jacobs, T.; Dera, R.; D’Haen, J.; Manca, J.; Boyen, H.-G. (APL materials, 2014)
Organometal trihalide perovskite solar cells arguably represent the most auspicious new photovoltaic technology so far, as they possess an astonishing combination of properties. The impressive and brisk advances achieved so far bring forth highly efficient and solution processable solar cells, holding great promise to grow into a mature technology that is ready to be embedded on a large scale. However, the vast majority of state-of-the-art perovskite solar cells contains a dense TiO2 electron collection layer that requires a high temperature treatment (>450 °C), which obstructs the road towards roll-to-roll processing on flexible foils that can withstand no more than ∼150 °C. Furthermore, this high temperature treatment leads to an overall increased energy payback time and cumulative energy demand for this emerging photovoltaic technology. Here we present the implementation of an alternative TiO2 layer formed from an easily prepared nanoparticle dispersion, with annealing needs well within reach of roll-to-roll processing, making this technology also appealing from the energy payback aspect. Chemical and morphological analysis allows to understand and optimize the processing conditions of the TiO2 layer, finally resulting in a maximum obtained efficiency of 13.6% for a planar heterojunction solar cell within an ITO/TiO2/CH3NH3PbI3-xClxpoly(3-hexylthiophene)/Ag architecture.